Modelagem computacional e análise das propriedades termodinâmicas do líquido super-resfriado do sistema Fe-Nb-B - Alvares, Ebert Daniel Macedo (2019)
Amorphous alloys of the Fe-Cr-Nb-B system are promising materials to supply the demand for new pipe coatings of higher wear resistance in the petrochemical industry due to its good abrasion and corrosion resistance properties. Since the development of the CALPHAD method, which is able to calculate the thermodynamic properties of several materials through computational methods, the development of new metallic alloys has been accompanied by modeling and calculations of phase stability and transformation in this framework. In order to predict the stability and tendencies of transformations of amorphous alloys of the Fe-Nb-B system, the two-state model recommended at the Ringberg 95 workshop to describe the amorphous state is applied in the CALPHAD framework to extrapolate the thermodynamic properties of this phase of the Fe-Nb-B system to ranges far below the melting temperature. The new calculated phase diagram shows good agreement to the recently reported phase diagram of the Fe-Nb-B system and more accurate and physically consistent when evaluating the heat capacity, entropy, and heat of crystallization at low temperature. These properties are compared with the experimental data reported in the literature and with new thermodynamic data of the amorphous alloy Nb84B16 obtained from differential scanning calorimetry in this work.